Targeting separate specific learning parameters underlying cognitive behavioral therapy can improve perceptual judgments of anger. (December 2019) - Lynn, Spencer K.; Bui, Eric; Hoeppner, Susanne S.; O'Day, Emily B.; Palitz, Sophie A.; Barrett, Lisa F.; Simon, Naomi M.
Abstract: Background and objectives: Anxiety disorders are characterized by biased perceptual judgment. An experimental model using simple verbal instruction to target specific decision parameters that influence perceptual judgment was developed to test if it could influence anger perception, and to examine differences between individuals with social anxiety disorder (SAD) relative to generalized anxiety disorder (GAD) or non-psychiatric controls. Methods: Anger perception was decomposed into three decision parameters (perceptual similarity of angry vs. not-angry facial expressions, base rate of encountering angry vs. not-angry expressions, payoff for correct vs. incorrect categorization of face stimuli) using a signal detection framework. Participants with SAD (n = 97), GAD (n = 90), and controls (n = 98) were assigned an instruction condition emphasizing one of the three decision parameters. Anger perception pre- vs. post-instruction and its interaction with diagnosis were examined. Results: For all participants, base rate instructions impacted response bias over and above practice effects, supporting the validity of this instructional task-based approach to altering response bias. We failed to find a similarity or payoff instruction effect, nor a diagnosis interaction. Limitations: Future instructional tasks may need to more closely target core cognitive and perceptual biases in anxiety disorders to identify specific deficits and how to optimally influence them. Conclusions: This study demonstrates that specific decision parameters underlying perceptual judgment can be experimentally manipulated. Although our study failed to show diagnosis specific effects, it suggests that individual parameter "estimation" deficits may be experimentally isolated and potentially targeted, with the ultimate goal of developing an objective approach to personalized intervention targeting biased perceptual judgments in anxiety disorders. Highlights: Signal detection theory was applied to experimentally influence perceptual judgment. Simple instruction targeting a decision parameter influenced anger perception. Base rate instruction impacted response bias across anxiety disorders and controls. Specific parameter estimation deficits may be experimentally isolated and targeted. Future tasks should target specific biased perceptual judgment in anxiety disorders.